1421. Assessing Serious Infections Common in Persons Who Inject Drugs in the United States and Tennessee. (31st December 2020) - Lowry, Michael; Fiske, Christina; Rebeiro, Peter F
Abstract: Background: The opioid crisis is a public health emergency in the United States (US) and Tennessee (TN), and injection drug use predisposes users to a variety of serious infections. We therefore examined infection rates among persons who inject drugs (PWID) from 2001-2014 in the US and TN. Methods: We conducted an ecological study using publicly available data including discharge diagnosis codes: the Healthcare Cost and Utilization Project (HCUP). We identified all persons from 2001-2014 with ICD-9 codes for bacterial infections common among PWID: endocarditis (IE), osteomyelitis (OM), septic arthritis (SpA), and skin/soft tissue infections (SSTI). We calculated rates of substance use and infection among all hospital discharges. Spearman's rank correlation quantified the relationship between infection and reported hepatitis C seropositivity (HCV), Substance Abuse (SA) and opioid use disorder (OUD) rates. Poisson regression yielded incidence rate ratios (IRR) and 95% confidence intervals [-], and restricted cubic splines were fit to assess annual trends flexibly. Results: Unadjusted rates of both substance use and infection among those discharged from hospitals were higher in the US overall than in TN from 2001-2014 (p< 0.05) (Figure 2, 3). Overall infections, HCV (IRR=1.14 [1.12-1.17]), SSTI, OM, and SpA increased annually in the US; overall infections, HCV (IRR=1.14 [1.10-1.15]), and SSTI increased in TN. OUD (IRR=0.96 [0.94-0.98]) and IE (IRR=0.97 [0.97-0.98]) decreased in the US (Table 1). In the US, there were strong positive correlations between any other infection and HCV (ρ=0.87), IE and OUD (ρ=0.7), SSTI and HCV (ρ=0.9), OM and HCV (ρ=0.69), and SpA and HCV (ρ=0.68); IE was negatively correlated with HCV (ρ=-0.84). In TN, overall infections (ρ=0.68), and specifically SSTI (ρ=0.62), were correlated with HCV (Figure 1). Table 1 Figure 1 Figure 2 Conclusion: Serious infections common in PWID are increasing in TN and the US; they correlate with HCV rates, which have risen significantly in hospitalized patients. Interestingly, opioid use disorder incidence from discharge data declined from 2001-2014 for both TN and the US, which may be due to coding lapses or shifts in type of opioid use with no well-known billing code. However, we must continue monitoring and mitigating both substance use and its sequelae. Disclosures: All Authors : No reported disclosures